Liver Abscess due to Enterohepatic Migration of Fish Bone - Hoque, Md Mohimanul; Haque, Md Azizul; Islam, Md Shafiqul; Rahman, Md Hafizur; Rahman, Md Anisur; Haque, ANM Mozammel (TAJ: Journal of Teachers Association, 2020)
Liver abscess due to accidentally ingested fish bone is extremely rare; only 30 cases have been described in the literature. We are reporting a 46-year-old female presenting with liver abscess due to enterohepatic migration of accidentally ingested fish bone. TAJ 2020; 33(1): 48-50